The extent of HLA-DR expression on HLA-DR+ Tregs allows the identification of patients with clinically relevant borderline rejection - Schaier, Matthias; Seissler, Nicole; Becker, Luis Eduardo; Schäfer, Sebastian Markus; Schmitt, Edgar; Meuer, Stefan; Hug, Friederike; Sommerer, Claudia; Waldherr, Rüdiger; Zeier, Martin; Steinborn-Kröhl, Andrea (Transplant international, 2013)
Regulatory T cells (Tregs) were shown to be involved into the pathogenesis of acute rejection after transplantation. The suppressive activity of the total regulatory T cell pool depends on its percentage of highly suppressive HLA-DR+-Treg cells. Therefore, both the suppressive activity of the total Treg pool and the extent of HLA-DR expression of HLA-DR+-Tregs (MFI HLA-DR) were estimated in non transplanted volunteers, patients with end-stage renal failure (ESRF), healthy renal transplant patients with suspicion on rejection, due to sole histological Bord-R or sole acute renal failure (ARF), and patients with clinically relevant borderline rejection (Bord-R and ARF). Compared to patients with only Bord-R or only ARF, the suppressive activity of the total Treg cell pool was exclusively reduced in patients with clinically relevant Bord-R. In parallel, the HLA-DR MFI of the DR+-Treg subset was significantly decreased in these patients, due to a significantly lower proportion of DRhigh+-Tregs, which were shown to have the highest suppressive capacity within the total Treg pool. Our findings clearly demonstrate that the determination of the HLA-DR MFI of the HLA-DR+-Treg subset allows a highly sensitive, specific and non-invasive discrimination between patients with clinically relevant Bord-R (Bord and ARF) and patients with subclinical rejection or other causes of transplant failure.